2007
DOI: 10.2220/biomedres.28.239
|View full text |Cite
|
Sign up to set email alerts
|

pH stat studies on bicarbonate secretion in the isolated mouse ileum

Abstract: Bicarbonate secretion occurs in almost all segments of the gastrointestinal tract. This study examined HCO 3 − secretion in the ileum, since it is less understood than HCO 3 − secretion in other intestinal segments. Mouse ileal mucosa was mounted in vitro in Ussing chambers, and the mucosal alkalinization rate (J OH ) was determined by pH stat titration, while the mucosal side was bathed with a buffer-free solution (100% O 2 ) and the serosal side with a HCO 3 − /CO 2 -buffered solution. The transmural potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
3
3
0
Order By: Relevance
“…B and B), and consistent with the abolition of DIDS‐sensitive (mucosal Cl − ‐dependent) HCO3 secretion by the mouse distal ileum following the removal of serosal HCO3/CO 2 (Uchiyama et al. ; Zhang et al. ).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…B and B), and consistent with the abolition of DIDS‐sensitive (mucosal Cl − ‐dependent) HCO3 secretion by the mouse distal ileum following the removal of serosal HCO3/CO 2 (Uchiyama et al. ; Zhang et al. ).…”
Section: Discussionsupporting
confidence: 76%
“…This notion was corroborated by the inability of CA inhibitor ethoxzolamide to impact Cl À fluxes (Figs. 3B and 5B), and consistent with the abolition of DIDS-sensitive (mucosal Cl À -dependent) HCO À 3 secretion by the mouse distal ileum following the removal of serosal HCO À 3 /CO 2 (Uchiyama et al 2007;Zhang et al 2007). A role for CA in the mouse ileum cannot be dismissed entirely as Uchiyama et al (2007) observed that Cl À -dependent HCO À 3 secretion was reduced~30% in the presence of 100 lmol/L acetazolamide.…”
Section: Effects Of Acid-base Variables On CL à Transport By the Moussupporting
confidence: 73%
See 2 more Smart Citations
“…Quercetin could have exerted its’ effect through the GP-ACII-CAMP signaling pathways that is known to participate in ion channels/membrane transporters’ functions [ 27 , 28 ] ACII-GP-cAMP has been shown to be involved in CFTR and SLC26A6 activation which could lead to the increased in HCO 3 - secretion. [ 29 ]. cAMP is required for SLC26A6 and CFTR functions in the pancreas and salivary ductal epithelial cell [ 30 ].…”
Section: Discussionmentioning
confidence: 99%